Short versus long double-stranded RNA activation of a post-transcriptional gene knockdown pathway. Issue 12 (2nd December 2017) - Shpak, Nir; Manor, Rivka; Abilevich, Lihie Katzir; Mantal, Ortal; Shavit, Keshet; Aflalo, Eliahu D.; Toiber, Debra; Sagi, Amir
ABSTRACT: RNA interference (RNAi) utilizes a conserved cellular autoimmune defense mechanism involving the internalization of dsRNA into cells and the activation of a set of RNAi related genes. Using RNAi, complete sex reversal is achievable in males of the prawn Macrobrachium rosenbergii by knocking down the transcript level of an insulin-like androgenic gland hormone ( Mr-IAG ) through injections of dsRNA of the entire Mr-IAG ORF sequence (ds Mr-IAG – 518bp). Interestingly, in-vivo knockdown success and ds Mr-IAG lengths seemed to correlate, with long dsRNA being the most effective and short dsRNA fragments showing no effect. However, little is known about the RNAi machinery in M. rosenbergii . We discovered the Mr-Dicer and Mr-Argonaute gene families, associated with the major knockdown pathways, in our M. rosenbergii transcriptomic library. In response to ds Mr-IAG administration, only post-transcriptional pathway-related gene transcript levels were upregulated. In addition, a passive dsRNA channel (a SID1 gene ortholog) that allows external dsRNA to enter cells was found. Its function was validated by observing Mr-SID1 specific upregulation dependent on dsRNA lengths, while attempted loss-of-function experiments were lethal. Our results, which suggest differential systemic responses to dsRNA lengths, provide evidence that the above RNAi-based manipulation occurs via the post-transcriptional pathway. The temporal nature of the latter pathway supports the safety of using such RNAi-based biotechnologies in aquaculture and environmental applications. Unlike reports of RNAi driven by the administration of small dsRNA fragments in-vitro, the case presented here demonstrates length dependency in-vivo, suggesting further complexity in the context of the entire organism.